Clinical utility of (99mTc)‐TRODAT‐1 scans to differentiate Parkinsonian syndromes: case studies and commentary. Issue 9 (4th September 2018) - Wong, Daniel; Veitch, Peter; Schembri, Geoff
Abstract: The differential diagnosis of Parkinsonian syndromes is challenging, especially in the elderly as they often have complex presentations. Nuclear imaging modalities can increase diagnostic accuracy. Single‐photon emission tomography (SPECT) using the ligand ( 99m Tc)‐TRODAT‐1 is used overseas but is yet to be approved in Australia. Three pilot cases of clinically unclear Parkinsonian syndromes from the Royal North Shore Hospital Aged Care Department who underwent ( 99m Tc)‐TRODAT‐1 scans are described. From experience overseas, the ( 99m Tc)‐TRODAT‐1 scan has clinical utility in the differential diagnosis of Parkinsonian syndromes. ( 99m Tc)‐TRODAT‐1 has a lower cost and greater availability than other ligands. Our initial scan findings are largely consistent with the clinical picture, but low specific binding can affect scan interpretation. ( 99m Tc)‐TRODAT‐1 is a potential tool in the differential diagnosis of Parkinsonian syndromes. Further experience regarding its effect on patient outcomes and cost effectiveness is required before routine clinical use can be recommended.